Stability evaluation and reinforcement of ultra-high fill embankment slope of GRS - Ren, Chao; Song, Changjun; Wu, Lijian; Fan, Hua; Zhang, Qiang; Li, Peng; Han, Zhijie; Yang, Jinkun (Frontiers in Earth Science, 2025)
The deformation and instability of embankment slope is one of the common engineering diseases in highway engineering. After the disaster occurs, it is easy to cause huge economic losses and casualties. Therefore, it is of great significance and value to carry out the stability evaluation of embankment slope for improving the quality of engineering and ensuring the safety of con-struction. In view of this, this paper took the super-high fill embankment slope project of the 8th section of Cangrong Expressway in Rongxian County, Guangxi, China as the research object. Firstly, a set of three-level stability evaluating indicator system of super-high fill embankment slope of GRS(granite residual soil) including 1 target layer, 4 criterion layers and 23 indicator layers was proposed, and a qualitative and quantitative evaluating indicator framework was established. Then, GT (Game Theory) was used to combine the sovereignty weight of AHP (Analytic Hierarchy Process) and the objective weight of EWM (Entropy Weight Method) to obtain a more compre-hensive combination weight value. Finally, combined with the indicator framework and the combination weight, the stability of the ultra-high fill embankment slope of the project was evaluated. The results showed that the embankment slope was basically stable, and landslide ac-cidents might occur during the construction process. Therefore, according to the relevant param-eters proposed in the indicator layer, the combined design methods and prevention and control measures of construction anti-slide retaining wall, subgrade cement mixing pile, dynamic com-paction reinforcement and geogrid were put forward from the three aspects of drainage, anti-slide means and soil reinforcement. The above treatment was to improve the short-term anti-sliding ability and long-term stability of the embankment slope under unfavorable conditions. So far, the reinforcement measures have been proved to be effective, and no landslide accident has occurred after the reinforcement is completed. The relevant research results can provide reference for similar projects such as stability evaluation and prevention and control measures of high fill embankment slope.